Design and Engineering of Microreactor and Smart-Scaled Flow Processes - Volker Hessel (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Microreactors are small devices with sub-millimeter internals which have superb mass and heat transfer. Initially, they were used for reactions with very high demands on the latter, e.g. very exothermic reactions, gas-liquid reactions with interfacial transport issues, reactions with very fast kinetics which demands even faster mixing, and more. In this way, the processing window was opened widely and, also due to the minute volumes only present in the reaction zone, safe processing under otherwise hazardous conditions was enabled. This includes processing of reactions which are prone to thermal runaway and in the explosive regime. Scale-up of promising reactions and products which was hindered with conventional technology is now possible using the new equipment. This has widened the process development possibilities in chemical industry. In the last years, micro process technology was not only used for the very problematic synthetic issues which formerly had a dead-end position in industry's process development. Rather, the scope of chemical reactions to be processed in microreactors was considerably widened by exploring new process conditions with regard to temperature, pressure, concentration, solvents, and more. This is commonly referred to as flow chemistry. This allowed to reduce the processing time-scale for many reactions to the minute range or even below which fits well to the residence times of microreactors. In addition, the process integration of several reactions in one flow to a multi-step synthesis has opened a new door in molecular diversity as well as system and process complexity. The same holds for the combination of reactions and separations in micro-flow. To achieve throughputs relevant for industrial production, smart scale-out to milli-flow units has established and supplemented the numbering-up concept (parallelization of microchannels/-reactors operated under equal conditions). New innovations and enabling technologies need anyhow evaluation and benchmarking with conventional technology on the full-system level. Yet, microreactor technology has in the last years deepened so much into process intensification on a holistic scale that the focus increasingly is given towards the process dimension-to process design and automation, real-case applications, cost analysis, life-cycle assessment, and more. The impact on cost competitiveness and sustainability becomes well assessed. Facing this very recent scientific achievement, the special issue "Design and Engineering of Microreactor and Smart-Scaled Flow Processes" of the journal Processes aims to cover recent advances in the development of microreactor and smart-scaled flow processes towards the process level - in the sense as given above.